Board independence, women directors and firm performance in Malaysian small-cap firms (Journal of Social Economics Research, 2024)
This study examined how board independence and female directors (i.e., women in leadership) affected the performance of Malaysian small-cap firms. Small-cap firms trading on the Bursa Malaysia ACE (Access, Certainty Efficiency) market were the subject of this study due to the less strict listing standards imposed on them than large-listed firms. The 2012-2014 annual reports of firms listed on the ACE market were downloaded through the Bursa Malaysia website and the required data was hand-collected. The hypotheses were tested using quantile regression (QR). The data reveal that board independence and firm performance are unrelated unless company performance is in the 0.10 quantile. Board independence has a negative impact on business performance at the 0.10 quantile.  Similarly, the connection between women directors and business success was negative in the lower quintiles particularly in the 0.10 and 0.30 quantiles. Nevertheless, in other quantiles, board independence and the presence of female directors on firm performance were not associated. The significance of the study lies in the possibility that small firms might find it excessively expensive to comply with the Malaysian Code of Corporate Governance (MCCG).   This study examines the hitherto ignored roles of board independence and women directors in small-cap enterprises on firm performance.